Koleksi Kumarasamy - Gopal, B.; Thaiveegan, K. (University of Malaya Library, 1986)
Lists 314 books owned by S.P.S. Kumarasamy donated by his brother G.K. Sinniah to The Tamil Collection at the University of Malaya Library. Kumarasamy was born in India in 1916 and came to Malaya in 1939.